Role of some N-containing compounds in chilling tolerance of maize - Páldi, Emil (Acta Biologica Szegediensis, 2002)
The paper reports on the effect of low temperature on the synthesis of a number of N-containing compounds in five inbred maize lines with different degrees of chilling tolerance. The compounds analysed are used as stress markers on the basis of their response to abiotic stress factors. The aim of the experiments was to obtain a better understanding of the role of these compounds in maize chilling tolerance. The results indicate that changes of various magnitudes occur in the quantities of putrescine, agmatine, glycine-betain and proline as the result of chilling treatment. The quantitative changes are correlated with the chilling tolerance of the given inbred maize lines. The alternative pathway of polyamine synthesis plays a substantial role in the development of the defence mechanism against low temperature.